Pengaruh Rasio Massa Pineapple Leaf Fiber yang Rendah Terhadap Kekuatan Tarik pada PALF/PP Composite - Moch. W Arif Sektiono; Saiful Arif; Jundan Hawariyyun; Rima Zidni Karimatan Nisak (Infotekmesin, 2026)
This study investigates the influence of a very low mass fraction of pineapple leaf fibers (PALF) (≤ 5 wt%) on the mechanical properties of polypropylene (PP)-based composites. The PALF fibers fill the PP matrix and thus influence the mechanical properties of the composite. To improve fiber-matrix adhesion, the PALF fibers were first pretreated for 2 hours in a 5% NaOH solution. The composites were produced using a hand lay-up process, in which the PALF fibers were placed in the mold, and the PP matrix was subsequently injection-molded into the mold at 200 °C. The mass ratios of PALF to PP were 0%:100%, 1%:99%, 2%:98%, 3%:97%, 4%:96%, and 5%:95%. The mechanical properties were tested using a tensile test on a dumbbell-shaped specimen and determined according to DIN EN ISO 527-4 to establish the tensile strength (TS) and tensile modulus (TM). The results showed that adding up to 5 wt% PALF increased tensile strength by 94.74% and tensile modulus by 181.97% compared to pure, fiber-free PP. The highest values for tensile strength (32.31 MPa) and tensile modulus (17.2 × 10⁻⁴ GPa) were achieved with a 5% PALF composition. These results indicate that even small fiber content effectively improves the mechanical properties of composite materials and makes them suitable for the production of lightweight and flexible materials such as biomechanical and prosthetic components